Identification of RNA silencing suppressor encoded by wheat blue dwarf (WBD) phytoplasma. (31st May 2021) - Wang, L.; Chen, W.; Ma, H.; Li, J.; Hao, X.; Wu, Y.
Abstract: Plants possess an innate immune system for defence against pathogens. In turn, pathogens have various strategies to overcome complex plant defences. Among diverse pathogens, phytoplasmas are associated with serious diseases in a range of species. RNA silencing serves as an efficient defence system against pathogens in eukaryotes but can be interrupted by RNA silencing suppressors (RSSs) encoded by pathogens. Currently, many RSSs have been identified in viruses, bacteria, oomycetes and fungi. Phytoplasmas are pathogens in several hundred plant species. In this research, 37 candidate effectors of wheat blue dwarf (WBD) phytoplasma were screened for presence of RSS. Agro‐infiltration assay, yeast expression system, floral‐dip method for constructing transgenic A. thaliana, Western blotting and RT‐qPCR were used for identification of RNA silencing suppressors. SWP16 encoded by WBD phytoplasma was found to be a secretory protein that inhibited accumulation of GFP siRNA and led to the accumulation of GPF mRNA in systemic N. benthamiana 16c. Furthermore, in A. thaliana SWP16 inhibited production of miRNAs, which are components of RNA silencing. SWP16 also promoted infection of potato virus X. We conclude that SWP16 encoded by WBD phytoplasma was an RSS, suppressing systemic RNA silencing. This is the first evidence that a phytoplasma encodes an RSS and provides a theoretical basis for research on the interaction mechanisms between pathogens and plants. Abstract : A secretory protein SWP16 encoded by wheat blue dwarf (WBD) phytoplasma was found to suppress systemic RNA silencing and promote infection of potato virus X (PVX).